2023
DOI: 10.1021/acs.jmedchem.3c00954
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Esculetin–Furoxan–DEAC Ternary Hybrids for Anti-Triple Negative Breast Cancer

Mingju Wen,
Jianbo Sun,
Miao Yang
et al.

Abstract: Twelve new hybrid compounds of Esculetin with nitric oxide (NO) donors and/or mitochondrial targeting groups were designed, synthesized, and evaluated for their anti-tumor activity and mechanism in vitro and in vivo. Notably, the most potent compound A11 exhibited nanomolar antiproliferative activity on triple-negative breast cancer (TNBC) MDA-MB-231 cells (IC 50 = 8 nM) with a strikingly selective inhibitory effect. The mechanism of A11 involves targeting MDA-MB-231 cells' mitochondria, releasing a high NO co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Esc has shown notable anticancer properties against CRC cells, as evidenced by its ability to inhibit cell proliferation, induce apoptosis, arrest the cell cycle in the G 1 phase, reduce metastatic potential and decrease reactive oxygen species (ROS) production ( 15 17 ). Furthermore, in Esc-treated cell lines such as HCT116, HT-29 and DLD-1, inhibition of proliferation in these cell lines in a dose- and time-dependent manner was consistently observed ( 9 14 ). Choi et al ( 16 ) reported that Esc selectively targets cancer cells, sparing normal colonic epithelial cells.…”
Section: In Vitro Anticancer Properties Of Escmentioning
confidence: 92%
See 4 more Smart Citations
“…Esc has shown notable anticancer properties against CRC cells, as evidenced by its ability to inhibit cell proliferation, induce apoptosis, arrest the cell cycle in the G 1 phase, reduce metastatic potential and decrease reactive oxygen species (ROS) production ( 15 17 ). Furthermore, in Esc-treated cell lines such as HCT116, HT-29 and DLD-1, inhibition of proliferation in these cell lines in a dose- and time-dependent manner was consistently observed ( 9 14 ). Choi et al ( 16 ) reported that Esc selectively targets cancer cells, sparing normal colonic epithelial cells.…”
Section: In Vitro Anticancer Properties Of Escmentioning
confidence: 92%
“…In addition, in colorectal cancer, the IC 50 for 48 h in HT-29 cells was 55 µM ( 13 ), and the IC 50 for 24 h in HCT116 cells was 100 µM ( 13 ). Furthermore, the IC 50 of the designed compound in breast cancer, Esc-NO-DEAC ternary hybrid A11, was 8 nM for 48 h in MDA-MB-231 cells ( 14 ). Table I shows the different IC 50 values for Esc treatment in various cell lines.…”
Section: In Vitro Anticancer Properties Of Escmentioning
confidence: 99%
See 3 more Smart Citations